2020
DOI: 10.1021/acschembio.9b00700
|View full text |Cite
|
Sign up to set email alerts
|

Design and Discovery of Covalent α-GalCer Derivatives as Potent CD1d Ligands

Abstract: CD1d is a nonpolymorphic antigen-presenting protein responsible for the regulation of natural killer T (NKT) cell activation. α-Galactosyl ceramide (α-GalCer, KRN7000) is the representative CD1d ligand that can bind to the CD1d protein. The resulting complex is recognized by the T cell receptors of the NKT cell, inducing various immune responses. Previous structure–activity relationship studies of α-GalCer have revealed that the ability of NKT cells to induce cytokines depends on the ligand structure, and in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Further analyses revealed that compounds like 24 were appearing faster than αGalCer on the cell surface (measured by staining followed by flow cytometry or confocal microscopy), [80] thereby indicating faster kinetics of ligand−mCD1d complex presentation, in accordance with the studies from Porcelli and co‐workers [64] . Bringing the anchoring effect to an extreme, in 2020 the group of Fujimoto reported the covalent, verified by LC/MS‐MS, and IL‐4 skewing ligand 25 [82] . However, comparison of 24 and 25 revealed a similar cytokine response, raising questions regarding the role of the covalent linkage.…”
Section: αGalcer Analogssupporting
confidence: 71%
See 1 more Smart Citation
“…Further analyses revealed that compounds like 24 were appearing faster than αGalCer on the cell surface (measured by staining followed by flow cytometry or confocal microscopy), [80] thereby indicating faster kinetics of ligand−mCD1d complex presentation, in accordance with the studies from Porcelli and co‐workers [64] . Bringing the anchoring effect to an extreme, in 2020 the group of Fujimoto reported the covalent, verified by LC/MS‐MS, and IL‐4 skewing ligand 25 [82] . However, comparison of 24 and 25 revealed a similar cytokine response, raising questions regarding the role of the covalent linkage.…”
Section: αGalcer Analogssupporting
confidence: 71%
“…[64] Bringing the anchoring effect to an extreme, in 2020 the group of Fujimoto reported the covalent, verified by LC/MS-MS, and IL-4 skewing ligand 25. [82] However, comparison of 24 and 25 revealed a similar cytokine response, raising questions regarding the role of the covalent linkage. It is important to note that studies of the anchoring effect primarily have been carried out with murine assays and that human models have not yet been investigated.…”
Section: Modification Of the Lipid Chainsmentioning
confidence: 99%
“…Porcelli’s graceful study revealed that Th1 glycolipids are loaded into CD1d molecules, which subsequently accumulate in lipid rafts on the APC plasma membrane, whereas Th2 glycolipids are loaded onto CD1d molecules, which are excluded from lipid rafts. As a result, Th2-biasing αGC analogues feature chemical modifications that increase polarity while decreasing hydrophobicity, such as shorter N-acyl chains and polar substitutions. , In addition to Porcelli’s findings, Fujimoto et al recently found that Th2-biasing glycolipids are those in which the lipid component contains polar groups capable of anchoring CD1d ligands. , Rather than being modified at lipid chains, αGC-CPOEt has a PEG-linked ethyl phosphonate at C-6′ position, which is more hydrophilic than αGC and produced an increased level of IL-4. The correlation of hydrophilicity and Th2-selective cytokine production from αGC-CPOEt is consistent with Porcelli’s model.…”
Section: Discussionmentioning
confidence: 98%
“…Th2-polarizing iNKT cell agonists are attractive potential candidates for adjuvants and therapeutic drugs. In addition to C20:2 and OCH, other Th2-type αGC analogues with novel modifications have appeared in recent decades. , Unfortunately, the majority of them were evaluated in vitro, or assessed through serum levels of IFN-γ and IL-4 after intraperitoneal or intravenous injection of the glycolipids, or used as a single agent in autoimmune disease models (such as PBS-25, Bz amide-containing αGC derivative), with only a few Th2 analogues investigated as vaccine adjuvants (such as KBC009, , αGC-MPEG). Notably, even though an in vivo cytokine assay on serum revealed a Th2 cytokine profile, KBC009 and αGC-MPEG induced robust neutralizing antibody responses.…”
Section: Discussionmentioning
confidence: 99%
“…The other broadly studied part of the αGalCer was the lipid chains, exploring in both tails the length impact,[ 3 , 4 ] ramification or substitution, and the introduction of other groups such as aromatic rings,[ 5 , 6 , 7 , 8 ] polar groups [9] or halogens. Recently it was published a new derivative able to bind covalently to the CD1d antigen binding groove, increasing ligand affinity [10] and inducing a Th2 polarizing activity.…”
mentioning
confidence: 99%